Between Poetry and Painting: Giovanni Andrea dell’Anguillara’s Metamorfosi as a Model for Genoese Baroque Poets and Painters - Montanari, Giacomo (Actual Problems of Theory and History of Art, 2018)
In a large part of recent studies on baroque iconography, the development of mythological representations and the use of classical sources during the 17th century has been considered. When referring to the sources used by baroque painters, it is quite common to speak generically about “Ovid”, and in not many cases we found precise links to one of the edited texts of the Metamorfosi, which were largely used by painters instead of the original Latin version. In the same way, the new “baroque language” used by poets is founded too on the basis of classical poems, revisited by great literates of the 16th century: especially Tasso, Ariosto, and Anguillara. The more logical way of reading the roots of the baroque culture through objects, such as books and works of art, is to understand completely the cultural landscape in which both poets and painters lived and the sources they considered to be “classical” or “antico”: a perspective that is radically different from ours. The aim of this paper is to demonstrate how in Genoa, one of the greatest cities in which the new baroque culture rose, during the 17th century, the book by Anguillara was used both as a model by literates for their baroque rethorical composition and by painters as a more comprehensible and “modern” source of the “antico” for their works of art. The importance of Anguillara’s book is well demonstrated by its finding in the most important Genoese libraries of the 16th and 17th century, which have been checked in some recent publications. The great literary works by Luca Assarino and Anton Giulio Brignole Sale, and the painted myths by Orazio De Ferrari, Domenico Fiasella and Gregorio De Ferrari become, from this point of view, important examples of the communitas studiorum that was present in Genoa’s Republic all along the 17th century and that made the Ligurian city an important and today still less studied center of the European cultural update.